Comparison between DSQIID total / sub-item scores and plasma p-tau elevation in adults with Down's syndrome. - Makiko Shinomoto; Chisen Takeuchi; Harutsugu Tatebe; Fukiko Kitani-Morii; Takuma Ohmichi; Yuzo Fujino; Kanako Menjo; Naoto Terada; Miho Osako; Yoko Mochizuki; Satoshi Teramukai; Takahiko Tokuda; et al. (PLoS ONE)
The Dementia Screening Questionnaire for Individuals with Intellectual Disabilities (DSQIID) is an appropriate screening tool for detecting dementia in Down's syndrome patients. However, whether this questionnaire reflects the neuropsychiatric signs of biomarker-confirmed Alzheimer's disease in DS (DS-AD) remains unknown. To address this issue, we compared the plasma phosphorylated tau (P181tau: p-tau) level of a representative AD biomarker with the total score and each sub-score of the DSQIID. The DSQIID was completed by 43 of the 56 individuals enrolled in the study. The DSQIID total scores tended to be positively associated with age, and some sub-scores increased in an age-dependent manner. DSQIID total scores and some sub-scores were also positively correlated with plasma p-tau levels, while all significant correlations disappeared after adjusting for age. Moreover, one sub-score appeared to have a significant negative correlation with plasma p-tau levels after adjusting for age. The DSQIID likely reflects age-associated behavioral changes in patients with DS. Meanwhile, their scores did not correlate with plasma p-tau after adjusting for age, suggesting that there might be room for improvement in the DSQIID for detecting DS-AD.